Suicide Prevention in Kerala: The need to focus on middle-aged and aged men - P. Jayakumar & P.O. George
A basic analysis has been carried out to identify the most suicide prone segments of Kerala’s society, classified on the basis of age and gender. Official data on suicide incidence along with population figures from the Census have been used to calculate suicide rates for different age-gender groups for the year 2001. As expected, rate of suicide among males is found to be greater than those of females. The analysis also reveals that the suicide rate prevalent among males aged above 30 years is significantly higher than the state’s average. Even among them, the suicide rate found among males aged between 45 and 59 years is very high and exceeds 100 /100,000 of population level. To know thus that one in every one thousand senior men in Kerala is likely to exercise the option of ending life, emphasizes the needs to evolve effective suicide prevention strategies addressing such specific population groups